Sistema embarcado para o controle de acesso em áreas restritas de prédios inteligentes - Maciel, Hyuri S.; Silva, David F.; do Nascimento, Clóvis G. M.; Aquino, Andre L. L. (Proceedings of Brazilian Symposium on Ubiquitous and Pervasive Computing (SBCUP), 2016)
This paper presents an embedded system for access control in restricted area through the integration of two authentication strategies: facial recognition and RFID TAGs. Once that face recognition, in an embedded system, is susceptible to failures and RFIDs TAGs can be used by other users, the integration of these two solutions aims to increase the robustness of access control system. This system can be easily deployed into enterprise environments, meetings and offices rooms. Additionally the system proposed does not require the need to have the system connected to the Internet. Through the evaluations we observed an acceptable execution time and better robustness in access control system, even using simple techniques of face recognition.